2019
DOI: 10.1038/s41598-019-43669-7
|View full text |Cite|
|
Sign up to set email alerts
|

Quantified forces between HepG2 hepatocarcinoma and WA07 pluripotent stem cells with natural biomaterials correlate with in vitro cell behavior

Abstract: In vitro cell culture or tissue models that mimic in vivo cellular response have potential in tissue engineering and regenerative medicine, and are a more economical and accurate option for drug toxicity tests than animal experimentation. The design of in vivo -like cell culture models should take into account how the cells interact with the surrounding materials and how these interactions affect the cell behavior. Cell-material interactions are furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 84 publications
3
27
0
Order By: Relevance
“…Based on the results from the 2D DE differentiation experiments showing that 6-day DE induction is the most effective method ( Bogacheva et al, 2018 ), we performed 6-day DE differentiation of iPS(IMR90)-4 cells in three 3D conditions. Suspension culture in this study represents a biomaterial/scaffold-free 3D culture condition, while NFC hydrogel is an inert biomaterial that exhibits weak nonspecific interactions with cells ( Harjumaki et al, 2019 ). Conversely, BME interacts with stem cells and DE cells directly via cell membrane receptors, so it represents an active cell-interacting biomaterial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results from the 2D DE differentiation experiments showing that 6-day DE induction is the most effective method ( Bogacheva et al, 2018 ), we performed 6-day DE differentiation of iPS(IMR90)-4 cells in three 3D conditions. Suspension culture in this study represents a biomaterial/scaffold-free 3D culture condition, while NFC hydrogel is an inert biomaterial that exhibits weak nonspecific interactions with cells ( Harjumaki et al, 2019 ). Conversely, BME interacts with stem cells and DE cells directly via cell membrane receptors, so it represents an active cell-interacting biomaterial.…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing E-cadherin expression during DE differentiation ( D’Amour et al, 2005 ) further reduces cell–cell interactions, thereby contributing to disrupted spheroid morphology. In contrast, NFC hydrogel has negligible adhesion forces to stem cells ( Harjumaki et al, 2019 )—minimizing cell–matrix interactions. Thus, the predominance of cell–cell interactions may account for the well maintenance of the spheroid shape in NFC hydrogel ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study reported that variability in PEI toxicity seen in different cell lines is possibly due to the difference in physiology of the cells [18]. WRL 68 and HepG2 are both derived from liver exhibiting morphologic structures similar to hepatocytes [19,20]. Both liver derived cell lines are more affected by PEI toxicity possibly due to their comparable physiology.…”
Section: Resultsmentioning
confidence: 99%
“…4 This is in part due to it's virus-free nature, high proliferation rate and it's ability to perform many hepatic specific functions such as albumin secretion. [93][94][95] However, because it is relatively stable in vitro culture, it does not give a true reflection of primary culture. Future work is needed to access primary or stem cells derived hepatocytes to verify the effect of scaffolds on long-term in vitro culture while ensuring that variables such as fibre base size and pore size are taken into count.…”
Section: Discussionmentioning
confidence: 99%